Chromosome location of ISSR markers and genes controlling seed germination under drought stress in wheat-barley disomic addition lines - Farshadfar, Mohsen (Cellular and Molecular Biology, 2020)
Alien disomic addition lines are valuable genetic resources for breeding programs under wide hybridization. The present study was carried out to identify the chromosome location of ISSR markers and genes controlling seed germination under drought stress in wheat-barley disomic addition lines. Germination experiment was performed at 0, -4 bar and -8 bar levels in a completely randomized design with three replications. The Germination Index, Germination Percentage, Coefficient of Germination Velocity, Mean Germination Time, Mean Germination Daily, and Plantlet Growth Speed were measured. Based on karyotype analysis, the presence of addition chromosomes was confirmed. The IS10 (0.494) and IS15 (0.395) primers showed the greatest polymorphism among the addition lines. The primers amplified most parts of the chromosomes 2H, 3H, and 7H, indicating these ISSR primers are located on these chromosomes. It is also indicated that most of the genes responsible for the seed germination under drought stress are located on chromosomes 4H and 5H.